Cohomology of Number Fields - Neukirch, Jürgen; Schmidt, Alexander; Wingberg, Kay (Grundlehren der mathematischen Wissenschaften, A Series of Comprehensive Studies in Mathematics, 2008)
This second edition is a corrected and extended version of the first. It is a textbook for students, as well as a reference book for the working mathematician, on cohomological topics in number theory. In all it is a virtually complete treatment of a vast array of central topics in algebraic number theory. New material is introduced here on duality theorems for unramified and tamely ramified extensions as well as a careful analysis of 2-extensions of real number fields.